A teoria Zhong Yong e a cultura oriental: uma análise em narrativas alegóricas da literatura brasileira - Chen, Michelle Xiao Xu Yan (Universidade Federal de São Carlos, 2026)
This study examines the presence of characteristics of the Zhong Yong Theory, also known as the Doctrine of the Mean or the Middle Way, in allegorical narratives of Brazilian literature, establishing connections among culture, literature, and education. It is based on the understanding that fables and parables are important pedagogical tools for transmitting values, cultural traditions, and ways of understanding life in society. The study aimed to describe how the Zhong Yong Theory, an Eastern philosophical tradition, is represented in these narratives, compare it with values associated with Western culture, and analyze its educational and formative potential. This qualitative, exploratory, and descriptive study was based on a literature review encompassing research on the concept of culture, the characteristics of Eastern and Western cultures, the principles of the Zhong Yong Theory, and the role of allegorical narratives—particularly fables and parables—as cultural and educational instruments. Based on the theoretical framework, seven analytical categories were established: harmonious social relationships, appreciation of learning across generations, cultivation of virtues, pursuit of the collective good, avoidance of excess, hierarchy and clearly defined social roles, and the promotion of complementary rather than polarized relationships. Six fables reflecting Eastern values and three reflecting Western values were analyzed. The findings indicate that narratives embodying Eastern values consistently emphasize balance, wisdom, collectivism, moderation, and learning developed through the relationship between teacher and disciple. In contrast, the Western narratives analyzed privilege perspectives grounded in competition, individualism, and the logic of the survival of the fittest. The study concludes that allegorical narratives constitute important cultural and educational means for transmitting values and worldviews, thereby influencing individuals' moral and social development. Furthermore, the findings contribute to expanding the pedagogical potential of allegorical narratives as instruments for critical reflection and intercultural education.
The Zhong Yong theory and eastern culture: an analysis of allegorical narratives in brazilian literature
Keywords: Teoria Zhong Yong; Cultura oriental; Narrativas alegóricas; Zhong Yong theory; Eastern culture; Allegorical narratives; CIENCIAS HUMANAS; 4. Educação de Qualidade